Optimization of the Sheet Metal Base of a Toggle Clamp Using Finite Element Method - Kauyuka, Pendapala Kristof; Blessing, Emmanuel Kodzo; Qiu, Qian; Ayano, Jeremiah Damilola; Liu, Hanci (International Journal of Engineering and Management Sciences, 2021)
Optimization relates to the ultimate yield strength and the maximum stress incident on the current model under critical working conditions and finds through iterative processing a way to compensate for the strength requirement without going beyond the desired mass limits. In this paper, the horizontal sheet metal base of a horizontal toggle clamp is optimised for mass reduction using the finite element analysis in the computer aided design software. The sheet metal base material is the ANSI32 Steel. In the design software, it is designed with the thickness of 7 mm and it is intended to support a workload of up to 750 N. The constraints were a fixed point added at all the holes and at the bottom surface of the sheet metal base. A number of iterations were made for the 750N loading force across the base plate to run the simulation. For optimization, the aim was to minimize the mass of the base plate. The design parameters were Von Mises, factor of safety and displacement. The variables were the slots’ width and material thickness along the mid-surface of the sheet metal. The mass was reduced by more than thirty per cent overall.